Utilization of Medicinal Plants: Case Study in Kelayam Sub-village Manua Sadap Village Kapuas Hulu Regency - Fathul Yusro; Ernalinda Mangkoan; Yeni Mariani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Most of the people in the Kelayam sub-village, Manua Sadap village, come from the dayak Iban tribe. Their lives are close to the forest, and they still hold on to their cultural customs are undoubtedly interesting for research, primarily how they use the plants in the forest as part of their traditional medicine. This study aims to record and analyze the medicinal plants used by the people of the Kelayam sub-village, Manua Sadap village, Kapuas Hulu Regency. We conducted this research using a survey method with a sampling technique, and the respondents were selected with a snowball sampling. The results showed that the people of the Kelayam sub-village, Manua Sadap village used 21 medicinal plants for various treatments such as to treat wounds, skin diseases, muscle pain, hypertension, cholesterol, stomach pain, and to treat toothache. There are 17 families of medicinal plants used by the community, and the most dominant is from the Rubiaceae family. The highest utilization of plant parts is leaves (67%) by boiling (31%) and pounding (30%) and the use of plants by drunk and patched, each of which has the same value (32%). The data on medicinal plants in the Kelayam sub-village, Manua Sadap Village, adds to the wealth of knowledge of traditional medicinal plants in Kapuas Hulu Regency, especially in the Iban Dayak comunity.